Identification of Tangible and Intangible Management Conservation in Historical Mosque - Budhi Ajar, Seno (Anuário do Instituto de Geociências, 2025)
Tangible and intangible management conservation is needed to conservator historical places, this research prioritizing tangible heritage implies that the mosque is managed as a heritage building. This research is a comprehensive analysis of the management and conservation of tangible and intangible heritage in historical mosques, focusing on examples from Japan and Indonesia. It highlights the challenges of balancing functionality and authenticity in managing historical mosques and emphasizes the importance of professional and transparent mosque management. The research explores the changes in the authenticity of tangible and intangible attributes in historical mosques and the different needs and values associated with them. It also discusses the history and changes in design, materials, and function of four historical mosques, including the assessment of their authenticity at the architectural level. The role and management of the mosques are identified as crucial factors in preserving tangible and intangible heritage. The paper offers valuable insights into the preservation and management of historical mosques and their tangible and intangible heritage.